Promoting Reproducibility and Replicability in Political Science - Abel Brodeur; Kevin Esterling; Jörg Ankel-Peters; Natália S. Bueno; Scott Desposato; Anna Dreber; Federica Genovese; Donald P. Green; Matthew Hepplewhite; Fernando Hoces de la Guardia; Magnus Johannesson; Andreas Kotsadam; et al. (Institute for Replication (I4R), 2024)
This article reviews and summarizes current reproduction and replication practices in political science. We first provide definitions for reproducibility and replicability. We then review data availability policies for 28 leading political science journals and present the results from a survey of editors about their willingness to publish comments and replications. We discuss new initiatives that seek to promote and generate highquality reproductions and replications. Finally, we make the case for standards and practices that may help increase data availability, reproducibility, and replicability in political science.
Keywords: 330; Reproducibility; replicability; political science